2020
DOI: 10.1111/jfbc.13139
|View full text |Cite
|
Sign up to set email alerts
|

Butiá fruit extract (Butia eriospatha) protects against oxidative damage and increases lifespan onCaenorhabditis elegans

Abstract: Butiá (Butia eriospatha) is a fruit of a palm tree belonging to the family Arecaceae, native to South America. The aim of this study was to evaluate the antioxidant potential of butiá extract using Caenorhabditis elegans as animal model. Initially, we performed survival experiments, reproduction, resistance to oxidative stress (post or pre‐treatment with paraquat or hydrogen peroxide), longevity, superoxide dismutase, and catalase GFP reporters' expression. We observed that butiá extract did not affect the wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…This work showed that HAE-Sc can extend lifespan of C. elegans, as also has been observed for a number of plant extracts with anti-oxidative properties, such as those from blueberries (Wang et al, 2018), ginseng (Wang et al, 2021), Caesalpinia mimosoides (Rangsinth et al, 2019), and Butiá (Butia eriospatha) (Tambara et al, 2020), among other plants. This process has been proposed to be mediated by aging-related pathways that control activation of autophagy, mitochondrial biogenesis and the antioxidant machinery, among other mechanisms (Aman et al, 2021).…”
Section: Stress Resistance Assay (Heat Shock)supporting
confidence: 77%
“…This work showed that HAE-Sc can extend lifespan of C. elegans, as also has been observed for a number of plant extracts with anti-oxidative properties, such as those from blueberries (Wang et al, 2018), ginseng (Wang et al, 2021), Caesalpinia mimosoides (Rangsinth et al, 2019), and Butiá (Butia eriospatha) (Tambara et al, 2020), among other plants. This process has been proposed to be mediated by aging-related pathways that control activation of autophagy, mitochondrial biogenesis and the antioxidant machinery, among other mechanisms (Aman et al, 2021).…”
Section: Stress Resistance Assay (Heat Shock)supporting
confidence: 77%
“…The antioxidant potential in B. eriospatha was tested using the Caenorhabditis elegans animal model. Tambara et al (2020) observed that extracts of Butia palm were able to prolong nematode (C. elegans) life cycle by protecting and reversing hydrogen peroxideinduced oxidative damage. B. capitata species, on the other hand, demonstrated functionality as an inhibitor of colorectal cancer cells (HT-29) in an in vitro antitumor activity analysis (Lahlou et al, 2022).…”
Section: Physicochemical Properties and Nutritionmentioning
confidence: 99%
“…Additionally, it has been widely used for aging research and has conserved molecular and cellular pathways, which influence the longevity and stress tolerance. , According to previous reports, supplementation with fruit extracts, such as blueberries, raspberries, tart cherries, oranges, pomegranates, butia, apples, Zalema grape pomace, anthocyanin extract of acai, and mulberries, significantly delays aging in C. elegans by promoting the longevity, enhancing healthspan, and conferring stress resistance through various molecular pathways. In this current research, we extensively investigated the antiaging and anti-Parkinson’s effects of loquat fruit using C. elegans.…”
Section: Introductionmentioning
confidence: 99%